The fluid flow modeling procedure including a critically stressed fracture analysis of coalbed methane reservoir: a case study of Upper Silesian Coal Basin, Poland - Kępiński, Michał; Ryder, Paweł; Dudek, Jacek; Podsobiński, Daniel (Geology, Geophysics and Environment, 2023)
The geomechanical modeling turned out to be an essential component of the hydrocarbon exploration assisting reduction of risk of drilling issues and optimization of hydraulic fracturing treatment. This study provides a workflow of critically stressed fracture (CSF) analysis dedicated for coal layers. The main focus of the paper is applying the 1D mechanical models and following modelling of hydraulic fracturing treatment to describe the fracture behavior under the impact of the stresses at the wellbore scale. Another objective of the presented study is demonstration of benefits of 1D and 3D CSF analysis to understand fracture contribution to gained volume of hydrocarbon after fracturing of coal seam. Interpretation of fracture orientation and their behavior is vital to effective development of coal bed methane (CBM) resources as the CSF can be responsible for considerable part of CBM production. Natural fractures and faults contribute to fluid flow through rock. It is often noted that natural fractures may not be critically stressed at ambient stress state. However, during stimulation, the optimally oriented natural fracture sets have the inclination to become critically stressed. Hence, understanding of the recent stress state and fracture orientations is significant for well planning and fracturing design. The outcome of this study are comprehensive 1D mechanical Earth models (MEMs) for analyzed wells and explanation of behavior of identified CSF under variable stress state as well as understanding of the connectivity of natural fractures within zone subjected to fracturing treatment.